2020
DOI: 10.1111/odi.13664
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non‐surgical periodontal treatment on gingival crevicular fluid periostin levels in patients with gingivitis and periodontitis

Abstract: Objective The objective of the study was to evaluate the effect of non‐surgical periodontal treatment on gingival crevicular fluid (GCF) periostin levels in patients with gingivitis (G) and periodontitis (P). Subjects and methods A total of 90 subjects, 30 patients with P, 30 with G, and 30 periodontally healthy (H) subjects were included. Patients with periodontal disease received non‐surgical periodontal treatment. GCF periostin levels were assessed at baseline, at the 6th week, and the 3rd month after treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…These results may support the idea that periodontal inflammation can cause of periostin downregulation. However, in agreement with the present study, Arslan and co-workers found that periostin GCF levels decreased from the periodontitis group to the gingivitis and to the healthy control group [ 16 ]. As in the present study, samples had been taken from bleeding sites (GI = 2 and BOP positive).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results may support the idea that periodontal inflammation can cause of periostin downregulation. However, in agreement with the present study, Arslan and co-workers found that periostin GCF levels decreased from the periodontitis group to the gingivitis and to the healthy control group [ 16 ]. As in the present study, samples had been taken from bleeding sites (GI = 2 and BOP positive).…”
Section: Discussionsupporting
confidence: 93%
“…Periostin expression in the periodontal ligament is regulated by TGF-β, mechanical stress such as during mastication and tooth movement [ 11 ]. A study stated that periostin values increased in the presence of periodontitis in gingival crevicular fluid (GCF) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…PDLFs transfected with GFP-tagged periostin or an empty lentiviral expression vector were pretreated with 30 μM ML385 for 3 h, followed by 5 μg/ml LPS for 24 h. than that of the healthy group (Akman et al, 2018). Another study revealed the opposite result (Arslan et al, 2021). Our results indicated that increasing concentrations of LPS decreased the protein and mRNA expression levels of periostin.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, the level of periostin was also lower in peri‐implant sulcular fluid of peri‐implantitis than that of the healthy group(Akman et al, 2018). Another study revealed the opposite result (Arslan et al, 2021). Our results indicated that increasing concentrations of LPS decreased the protein and mRNA expression levels of periostin.…”
Section: Discussionmentioning
confidence: 90%
“…In the study conducted by Arslan R et al [ 27 ], the authors reported that the level of periostin in the GCF is significantly higher in people with periodontitis. Also, the level of periostin in the GCF of people with gingivitis was lower than the periodontitis group, but significantly higher than that of healthy people.…”
Section: Discussionmentioning
confidence: 99%